Coronary arterial origins in transposition of the great arteries: factors that affect outcome. A morphological and clinical study. Issue 3 (1st March 2000) - Li, J; Tulloh, R M R; Cook, A; Schneider, M; Ho, S Y; Anderson, R H
Abstract : OBJECTIVE: Transfer of the coronary arteries is crucial during the arterial switch operation for transposition, but little attention has been paid to the position of their orifices relative to the valvar sinuses. The objective of this study was to determine the factors which are important for effective transfer and to determine potential surgical significance. DESIGN: Morphological and clinical study. SETTING: Two national centres for neonatal cardiac surgery. PATIENTS: 277 patients with transposition of the great arteries. One group comprised 88 necropsy specimens (ages ranging from 17 weeks of fetal life to 17 years old), and the other comprised 189 children undergoing surgery. The coronary artery orifices were inspected relative to the depth of the aortic sinuses (vertical origin), relative to the commissures between the valvar leaflets (radial origin), and their angle of exit from the aortic wall (angle of origin). The data were compared with the surgical results. RESULTS: In the necropsy specimens, the vertical origin of the arteries was at, or above, the sinutubular junction in 20%, the radial origin was paracommissural in 3%, and the angle of origin was not orthogonal in 7%. Those with high take off and paracommissural origin were all intramural. In the clinical cases, those children with high take off, paracommissural origin or tangential origin had an increased risk at surgery. CONCLUSIONS: In 20% of hearts, high take off, paracommissural orifice, or tangential origin of coronary arteries is found. This may be recognised preoperatively by echocardiography and may cause technical difficulty in transfer during the arterial switch procedure.